Efektifitas peran financial literacy dan financial confidence bagi dosen PTMA di DKI Jakarta dalam meningkatkan financial well-being - Putri, Egidia Amalia; Amri, Andi (Universitas Negeri Surabaya, 2025)
This study aims to investigate how knowledge of financial literacy, financial trust impacts financial well-being. Using purposive sampling as many as 100 people. Data collection used online questionnaires distributed at Prof. DR. HAMKA Muhammadiyah University, Muhammadiyah Jakarta University, Muhammadiyah Business Institute, Muhammadiyah University of Science and Technology, Muhammadiyah University of Technology through social media. Data were analyzed using Smart PLS. The results showed that financial knowledge, financial behavior, and financial inclusion have a positive impact on financial well-being. The results of these findings provide important implications for the development of financial literacy education and training programs in the academic environment, as well as encouraging collaboration between educational institutions and financial institutions to improve lecturers' financial knowledge and skills. It is expected that PTMA lecturers can improve their financial well-being by increasing their financial knowledge and confidence. Ultimately, this will have a positive impact on their academic performance and teaching quality. It is hoped that this study will serve as a reference for future research and policy development.